Different Types of Mastoid Process Vibrations Affect Dynamic Margin of Stability Differently - Lu, Jiani; Xie, Haoyu; Chien, Jung Hung (Frontiers in Human Neuroscience, 2022)
The vestibular system is critical for human locomotion. In the past decades, these alternations of gait patterns have been majorly measured by the spatial-temporal gait parameters and respective variabilities. However, measuring gait characteristics can’t capture the full aspect of motor controls. Thus, additional measurement needs to be taken into consideration. This study proposed using the margin of stability (MOS) to identify the patterns of dynamic control under different types of mastoid vibrations in walking. This study hypothesized that 1) using the MOS method could understand another aspect of motor control induced by different types of mastoid vibrations, and 2) applying the mastoid vibrations could induce the asymmetric MOS. Twenty healthy young adults were recruited. Two electromechanical vibrotactile transducers were placed on the bilateral mastoid process to apply different types of vestibular vibrations (bilateral, unilateral, and no vibration). A motion capture system with eight cameras was used to measure the MOSap (margin of stability in the anterior-posterior direction), MOSml (margin of stability in the medial-lateral direction), and respective variabilities. The results showed both bilateral and unilateral mastoid vibration significantly increased MOSap and MOSml. Also, significantly larger MOSap, MOSml and respective variabilites were observed in the condition of the unilateral vibration than the condition of bilateral vibration. The result found that different types of mastoid vibrations affected the MOS differently. Besides, applying the unilateral mastoid vibrations induced a greater symmetric index of MOSml, suggesting that more active control in balance was needed in the medial-lateral than in the anterior-posterior direction.